Constructions of new integral graph families - Thomas Gardemann; Katja Mönius (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2021)
We construct new families of integral graphs by considering complete products, unions and point identifications of complete graphs and complete bipartite graphs. In particular, we find a relation between arithmetic series and the integrality of complete products.